Analysis of contact tracing surveillance for COVID-19 among healthcare workers in secondary referral hospital, Indonesia - Tri Pudy Asmarawati, - (Jurnal, 2022)
Background: Healthcare workers (HCWs) are more vulnerable to COVID-19 infection. Tracing and screening cases among healthcare workers are essential to overcome the spread of COVID-19. We held surveillance at the second-referral hospital in Surabaya, Indonesia, to inspect the associating factors of infected HCWs. Methods: From 776 HCWs, we conducted a structured retrospective review of all COVID-19-confirmed HCWs and ones having contact with COVID-19 patients between February-July 2021. We associated general characteristics (i.e age, gender, working sites, etc) of the sample with the positive cases, analyzed the vaccination status, then did bivariate and multivariate regression logistic analyses to determine related factors putting HCWs at risk for COVID-19 infection. Results: Bivariate analysis significantly revealed that 72.86% patients had a close contact (OR = 2.61; p<0.05), with medical staffs as the most frequent source (85.71%; OR = 2.19; p=0.033), for > 15 minutes contact duration (90%; OR = 1.1; p<0.05). Healthcare workers wearing proper PPE (N-95 and face shields) were significantly less exposed to COVID-19 (OR = 0.47; p<0.05; and OR = 0.46; p<0.05). Even fully-vaccinated samples were still prone to infection. (OR=1.25; p= 0.042). Common symptoms consisted of fever, rhinorrhea, sore throat, and vomiting (p=0.025l p=0.002; p<0.05; p=0.002). Multivariate regression logistic analysis disclosed that the use of N95 masks, contact duration >15 minutes, and the vaccine were the most influential factors (aOR = 1.72. 95% CI (1.029-2.88); aOR = 3.92. 95% CI (1.75-8.78); aOR = 0.39. 95% CI (0.13-0.82 )) Conclusions: Close contact, lack of compliance in wearing N95 masks, and unvaccinated status are risk factors for COVID-19 exposure to HCWs; thus, to achieve maximum prevention of intra-hospital transmission, the use of N-95 masks, contact avoidance, and vaccination, along with immediate tracing and strict health-protocols are all compulsory.